CULTURAL MEANING AND FUNCTIONS OF THE BERSIH DESA RITUAL IN DUKUH GENTAN BULU SUBDISTRICT, SUKOHARJO : Makna dan Fungsi Tradisi Bersih Desa di Dukuh Gentan Kecamatan Bulu, Sukoharjo - Brina Elberta Rosalina; Hafizh Maulana Syah Putra Putra; Rafiq Ahmad Fauzan; Salsabila (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Traditions are cultural heritage that contain religious, social, and cultural values while strengthening community identity. Rasulan is a local form of the Bersih Desa tradition preserved by the people of Dukuh Gentan,, Sukoharjo Regency. This study aims to analyze the meaning and functions of the Rasulan tradition in the context of local cultural preservation. This research employs a qualitative ethnographic approach using participatory observation, documentation, and in-depth interviews. The findings reveal three main functions of Rasulan: preserving cultural continuity through ritual practices, expressing a worldview centered on gratitude and collective prayers, and strengthening collective identity through social solidarity and mutual cooperation. The novelty of this study lies in examining Rasulan as a cultural strategy that sustains local identity amid modernization.